Das Abrahamopfer im Kontext von Gen 12-25 Narratologische und literarhistorische Untersuchungen - Rodrian, Jonathan (Mohr Siebeck, 2024)
A God who declares his promise null and void? Jonathan Rodrian examines the narrative of the »sacrifice of Isaac« against the background of the Abraham cycle. Considering the image of God, it becomes clear that Gods promise can be relied upon even when God himself seems to question his own commitment.
PublicationDate: 20240510
Keywords: Genesis -- Bindung Isaaks -- Erzvätererzählungen -- Vätererzählungen -- Sexuality -- Opferung -- Aqeda / Akedah -- 1. Mose -- Elohist -- AWZ (Ausschließliche Wirtschaftszone) -- Altes Testament